Unveiling the domino effect: a nine-year follow-up on pentalogy of central nervous system induced by a large unruptured cerebral arteriovenous malformation: a case report and literature review - He, Yunsen; Tao, Ye; Tian, Jing; Bao, Mingbin; Zhang, Mengjun; Huang, Qinjiang; Li, Hongliang; Chang, Xinxin; Li, Kun; Liu, Ping; Guo, Lili; Qin, Xiaohong; et al. (Frontiers in Neurology, 2024)
Background The disruption of intracranial fluid dynamics due to large unruptured cerebral arteriovenous malformation (AVM) commonly triggers a domino effect within the central nervous system. This phenomenon is frequently overlooked in prior clinic and may lead to catastrophic misdiagnoses. Our team has documented the world’s first case of so-called AVM Pentalogy (AVMP) induced by a AVM. Clinical presentation and result A 30-year-old female was first seen 9 years ago with an occasional fainting, at which time a huge unruptured AVM was discovered. Subsequently, due to progressive symptoms, she sought consultations from several prestigious neurosurgical departments in China, where all consulting neurosurgeons opted for conservation treatment due to perceived surgical risks. During the follow-up period, the patient gradually presented with hydrocephalus, empty sella, secondary Chiari malformation, syringomyelia, and scoliosis (we called as AVMP). When treated in our department, she already displayed numerous symptoms, including severe intracranial hypertension. Our team deduced that the hydrocephalus was the primary driver of her AVMP symptoms, representing the most favorable risk profile for intervention. As expected, a ventriculoperitoneal shunt successfully mitigated all symptoms of AVMP at 21-months post-surgical review. Conclusion During the monitoring of unruptured AVM, it is crucial to remain vigilant for the development or progression of AVMP. When any component of AVMP is identified, thorough etiological studies and analysis of cascade reactions are imperative to avert misdiagnosis. When direct AVM intervention is not viable, strategically addressing hydrocephalus as part of the AVMP may serve as the critical therapeutic focus.